2015
DOI: 10.1093/nar/gkv734
|View full text |Cite
|
Sign up to set email alerts
|

Transcription yield of fully 2′-modified RNA can be increased by the addition of thermostabilizing mutations to T7 RNA polymerase mutants

Abstract: On average, mutations are deleterious to proteins. Mutations conferring new function to a protein often come at the expense of protein folding or stability, reducing overall activity. Over the years, a panel of T7 RNA polymerases have been designed or evolved to accept nucleotides with modified ribose moieties. These modified RNAs have proven useful, especially in vivo, but the transcriptional yields tend to be quite low. Here we show that mutations previously shown to increase the thermal tolerance of T7 RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 39 publications
2
58
0
Order By: Relevance
“…Most recently, improved variants of the Chelliserrykattil and Ellington polymerase variant RGVG 82 were described by Meyer et al . 84 By including a series of stabilizing mutations into the enzyme, they were able to further increase the yields of 100% 2’OMe RNA transcriptions to levels approaching those observed for the wild-type polymerases using unmodified nucleotides. 84 …”
Section: Advancements In Aptamer Selection Technologymentioning
confidence: 99%
“…Most recently, improved variants of the Chelliserrykattil and Ellington polymerase variant RGVG 82 were described by Meyer et al . 84 By including a series of stabilizing mutations into the enzyme, they were able to further increase the yields of 100% 2’OMe RNA transcriptions to levels approaching those observed for the wild-type polymerases using unmodified nucleotides. 84 …”
Section: Advancements In Aptamer Selection Technologymentioning
confidence: 99%
“…Optimized conditions and the use of the Y639F/H784A double mutant of T7 RNAP has also enabled the transcription of oligonucleotides with increased levels of 2’-OMe substitutions, which have been used for the identification of stabilized aptamers against vascular endothelial growth factor (VEGF) [5] and staphylococcal protein A [6]. The recent discovery of additional T7 RNAP mutants that better recognize 2’-OMe substrates [7,8] and a mutant of the Syn5 RNA polymerase from cyanophage Syn5 that better recognizes 2’-F substrates [9] should facilitate the identification of stabilized aptamers in the future.…”
Section: Selex With Modified Rna and Dnamentioning
confidence: 99%
“…First, we explored the use of a mutant T7RNAP containing 10 mutations (termed ‘RGVG-M6’), including P266L, which exhibited a 25-fold increase in RNA yield of fully 2'-modified RNA over other commonly used mutant T7RNAPs. [7d] When we purified this mutant and tested the recombinant version in IVTs, we did not observe an increase in the total yield of 5'- th G-initiated RNAs. Second, we examined the effects of retaining the [ th G]:[GTP] ratio but increasing their absolute concentrations on T7RNAP P266L’s activity.…”
mentioning
confidence: 96%
“…[6] From this panel of mutants, we chose T7RNAP Pro266Leu (P266L) because kinetic and footprinting studies revealed that this mutant exhibits a delayed transition from transcriptional initiation to elongation and generates fewer aborted transcripts. [7] We sought to test the postulate that the T7RNAP P266L mutant would decrease aborted transcripts typically observed when 5'-G-analogs are used with T7RNAP wild-type (WT; Figure 2A ). The problem of low G-analog incorporation, however, necessitates a combination of transcriptional and post-transcriptional strategies since a fraction of transcripts will always be initiated with GTP.…”
mentioning
confidence: 99%
See 1 more Smart Citation